Privacy management and the role of instagram reels in da’wah: Insights from Muhammadiyah University Jakarta's students - Idris, Indriyani; Choirin, Muhammad; Fatoni, Nur; Iqbal, Mochammad (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - This study aims to investigate the optimization of social media for da'wah among students enrolled in the Islamic Communication and Broadcasting at the University of Muhammadiyah Jakarta. Method - Employing qualitative methods, particularly in-depth interviews, this research selects students aged 18–24 within the early adulthood category. Through a comprehensive analysis, it seeks to understand the nuances of privacy management in the process of personal disclosure on Instagram and examines the influence of satire and sarcasm on students' confidence levels. Result - The results of this study reveal that, overall, KPI-UMJ students exhibit effective privacy management during personal disclosure on Instagram. However, the prevalence of satire and sarcasm on the platform negatively impacts the confidence of students in sharing private narratives. Additionally, the research highlights the diverse views and motivations of students in optimizing Instagram for da'wah. Implication – The findings hold implications for both academia and practitioners involved in da'wah efforts on social media. Understanding the impact of satire and sarcasm on student confidence provides insights for educators and policymakers to develop strategies that foster a more conducive environment for private disclosures. Originality - This study contributes to the existing literature by offering nuanced insights into the challenges faced by KPI-UMJ students in optimizing Instagram for da'wah. The study's focus on the diverse motivations and perspectives of students in this context enhances the originality and depth of the research. *** Tujuan - Penelitian ini bertujuan untuk mengetahui optimalisasi media sosial untuk dakwah di kalangan mahasiswa yang terdaftar di Komunikasi dan Penyiaran Islam di Universitas Muhammadiyah Jakarta. Metode - Dengan menggunakan metode kualitatif, khususnya wawancara mendalam, penelitian ini memilih mahasiswa berusia 18-24 tahun yang termasuk dalam kategori dewasa awal. Melalui analisis yang komprehensif, penelitian ini berusaha untuk memahami nuansa manajemen privasi dalam proses pengungkapan diri di Instagram dan meneliti pengaruh sindiran dan sarkasme terhadap tingkat kepercayaan diri mahasiswa. Hasil - Hasil dari penelitian ini mengungkapkan bahwa, secara keseluruhan, mahasiswa KPI-UMJ menunjukkan manajemen privasi yang efektif selama pengungkapan diri di Instagram. Namun, prevalensi sindiran dan sarkasme di platform berdampak negatif pada kepercayaan diri mahasiswa dalam berbagi narasi pribadi. Selain itu, penelitian ini juga menyoroti beragamnya pandangan dan motivasi mahasiswa dalam mengoptimalkan Instagram untuk dakwah. Implikasi - Temuan penelitian ini memiliki implikasi bagi akademisi dan praktisi yang terlibat dalam upaya dakwah di media sosial. Memahami dampak sindiran dan sarkasme terhadap kepercayaan diri mahasiswa memberikan wawasan bagi para pendidik dan pembuat kebijakan untuk mengembangkan strategi yang mendorong lingkungan yang lebih kondusif untuk pengungkapan pribadi. Orisinalitas/Value - Penelitian ini berkontribusi pada literatur yang ada dengan menawarkan wawasan yang bernuansa tentang tantangan yang dihadapi oleh mahasiswa KPI-UMJ dalam mengoptimalkan Instagram untuk dakwah. Fokus penelitian ini pada motivasi dan perspektif mahasiswa yang beragam dalam konteks ini meningkatkan orisinalitas dan kedalaman penelitian.